2019
DOI: 10.5089/9781484388990.006
|View full text |Cite
|
Sign up to set email alerts
|

The Future of Saving

Abstract: EXECUTIVE SUMMARYOver the coming decades, declining fertility and increasing longevity will profoundly change the population age distribution in many countries, albeit at different paces. The fiscal consequences of this demographic transition have received considerable policy attention around the world, but what implications will it have for saving rates across countries? What role does the design of retirement systems play?This discussion note investigates how impending demographic shifts and the design of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 23 publications
(28 reference statements)
2
12
0
2
Order By: Relevance
“…Kuijs (2006) found evidence in China that savings rates are influenced significantly by certain determinants such as GDP per capita, credit to GDP ratio, real interest rate, public savings, old age dependency ratio, and share of industry in GDP, which are shown to be statistically significant. Amaglobeli et al (2019) found a negative and statistically significant relationship between the old age dependency ratio and private savings in 80 countries across the world by confirming the predictions from the life cycle model. Aron and Mihaescu (2014) explored the main variables of population savings in six CEE countries between 1995 and 2010.…”
Section: Literature Reviewsupporting
confidence: 79%
See 3 more Smart Citations
“…Kuijs (2006) found evidence in China that savings rates are influenced significantly by certain determinants such as GDP per capita, credit to GDP ratio, real interest rate, public savings, old age dependency ratio, and share of industry in GDP, which are shown to be statistically significant. Amaglobeli et al (2019) found a negative and statistically significant relationship between the old age dependency ratio and private savings in 80 countries across the world by confirming the predictions from the life cycle model. Aron and Mihaescu (2014) explored the main variables of population savings in six CEE countries between 1995 and 2010.…”
Section: Literature Reviewsupporting
confidence: 79%
“…The importance of demographic variables in the determination of savings may be confirmed by the findings of recent empirical research conducted by Deaton and Paxson (1992), Bosworth and Chodorow-Reich (2006), Ozcan, Gunay, and Ertac (2003), Horioka and Wan (2007), Gani and Yasin (2010), and Amaglobeli et al (2019). They empirically tested LCH and confirmed certain earlier findings that an increase in savings was caused by a higher rate of growth.…”
Section: Literature Reviewsupporting
confidence: 55%
See 2 more Smart Citations
“…Общей проблемой функционирования пенсионных систем является старение населения, данной проблеме уделяется внимание в работе М.Д. Амаглобели и его коллег [8]. Некоторые авторы, например, Ф. Чыбалски [9], изучают вопросы оценки эффективности пенсионной системы, другие, к примеру, Н. Ковал [10] [12].…”
unclassified